Noradrenergic tone mediates marble burying behavior after chronic stress and ethanol - den Hartog, Carolina R. (Psychopharmacology (Berl), 2020)
RATIONALE: Stress plays a major role in the development of alcohol use disorder (AUD) – a history of chronic stress contributes to alcohol misuse, and withdrawal from alcohol elevates stress, perpetuating cycles of problematic drinking. Recent studies have shown that, in male mice, repeated chronic intermittent ethanol (CIE) and stress elevates alcohol use above either manipulation alone, and impacts cognitive functions such as behavioral flexibility. OBJECTIVE: Here we investigated the impact of CIE and stress on anxiety in both sexes, and whether the norepinephrine (NE) system via locus coeruleus, which is implicated in both stress and alcohol motivation, is involved. RESULTS: Male and female mice received multiple cycles of CIE and/or repeated forced swim stress (FSS), producing elevated drinking in both sexes. CIE/FSS treatment increased anxiety, which was blocked by treatment with the α1-AR inverse agonist prazosin. In contrast, administration of the corticotropin releasing factor receptor antagonist CP376395 into locus coeruleus did not reduce CIE/FSS elevated anxiety. We also observed sex differences in behavioral responses to a history of CIE or FSS alone as well as differential behavioral consequences of prazosin treatment. CONCLUSIONS: These data indicate that NE contributes to the development of anxiety following a history of alcohol and/or stress, and that the influence of both treatment history and NE signaling is sex dependent. These results argue for further investigation of the NE system in relation to disrupted behavior following chronic alcohol and stress, and support the assertion that treatments may differ across sex based on differential neural system engagement.